Plasma phospholipid and dietary α-linolenic acid, mortality, CHD and stroke: the Cardiovascular Health Study. Issue 7 (27th August 2014) - Fretts, Amanda M.; Mozaffarian, Dariush; Siscovick, David S.; Sitlani, Colleen; Psaty, Bruce M.; Rimm, Eric B.; Song, Xiaoling; McKnight, Barbara; Spiegelman, Donna; King, Irena B.; Lemaitre, Rozenn N.
Abstract : Previous studies have suggested that long-chain n -3 fatty acids derived from seafood are associated with a lower risk of mortality, CHD and stroke. Whether α-linolenic acid (ALA, 18 : 3 n -3), a plant-derived long-chain essential n -3 fatty acid, is associated with a lower risk of these outcomes is unclear. The aim of the present study was to examine the associations of plasma phospholipid and dietary ALA with the risk of mortality, CHD and stroke among older adults who participated in the Cardiovascular Health Study, a cohort study of adults aged ≥ 65 years. A total of 2709 participants were included in the plasma phospholipid ALA analysis and 2583 participants were included in the dietary ALA analysis. Cox regression was used to assess the associations of plasma phospholipid and dietary ALA with the risk of mortality, incident CHD and stroke. In minimally and multivariable-adjusted models, plasma phospholipid ALA was found to be not associated with the risk of mortality, incident CHD or stroke. After adjustment for age, sex, race, enrolment site, education, smoking status, diabetes, BMI, alcohol consumption, treated hypertension and total energy intake, higher dietary ALA intake was found to be associated with a lower risk of total and non-cardiovascular mortality; on comparing the highest quintiles of dietary ALA with the lowest quintiles, the HR for total mortality and non-cardiovascular mortality were found to be 0·73 (95 % CI 0·61, 0·88) and 0·64 (95 % CI 0·52, 0·80), respectively. Dietary ALA was found to be not associated with the risk of cardiovascular mortality, incident CHD or stroke. In conclusion, the results of the present suggest study that dietary ALA, but not plasma phospholipid ALA, is associated with a lower risk of total and non-cardiovascular mortality in older adults.